2021
DOI: 10.1186/s12889-021-10765-1
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological trends in the burden of lung cancer attributable to PM2.5 exposure in China

Abstract: Objective PM2.5, which is a major contributor to air pollution, has large effects on lung cancer mortality. We want to analyse the long-term trends in lung cancer burden attributable to PM2.5 exposure and provide evidence that can be used for preventive measures and health resource planning. Methods Mortality data related to lung cancer were obtained from the Global Burden of Disease (GBD) 2019 project. A joinpoint regression analysis was used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…By querying the GBD database, we found that the latter contained 14 types of childhood cancer, as follows: liver cancer; tracheal, bronchus, and lung cancer (“lung cancer” in brief); colon and rectum cancer; lip and oral cavity cancer; nasopharynx cancer; malignant skin melanoma; ovarian cancer; testicular cancer; kidney cancer; brain and central nervous system (CNS) cancer; thyroid cancer; Hodgkin lymphoma; non-Hodgkin lymphoma; and leukemia ( 3 ). As with previously published articles, the related data are available to the public and can be extracted via the GBD Results Tool ( http://ghdx.healthdata.org/gbd-results-tool ) ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…By querying the GBD database, we found that the latter contained 14 types of childhood cancer, as follows: liver cancer; tracheal, bronchus, and lung cancer (“lung cancer” in brief); colon and rectum cancer; lip and oral cavity cancer; nasopharynx cancer; malignant skin melanoma; ovarian cancer; testicular cancer; kidney cancer; brain and central nervous system (CNS) cancer; thyroid cancer; Hodgkin lymphoma; non-Hodgkin lymphoma; and leukemia ( 3 ). As with previously published articles, the related data are available to the public and can be extracted via the GBD Results Tool ( http://ghdx.healthdata.org/gbd-results-tool ) ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis of lung adenocarcinoma was dominated by women and non-smokers, and subjects exposed to PM 2.5 were twice as likely to develop lung adenocarcinoma as other types of lung cancer [13]. In contrast, some studies have revealed that lung cancer incidence correlated with PM 2.5 was more significant for males [83,87]. The effect of age on PM 2.5 associated lung cancer remains controversial.…”
Section: Lung Cancermentioning
confidence: 99%
“…One cohort study on continued exposure to outdoor air pollution and lung cancer morbidity showed that PM 2.5 exposure had a greater effect among younger individuals [14]. Another study suggested that PM 2.5 was associated with increased mortality of lung cancer among older adults [87]. PM 2.5 can directly promote the proliferation, migration, and invasion of lung cancer cells [88][89][90].…”
Section: Lung Cancermentioning
confidence: 99%
“…The main sources of PM 2.5 are natural and anthropogenic sources, with anthropogenic sources accounting for the major part (Kim et al, 2015 ). Numerous studies have shown that PM 2.5 can cause not only respiratory diseases (allergic airway inflammation, asthma, and chronic obstructive pulmonary disease) (Choi et al, 2018 ; Weinmayr et al, 2018 ), but also diseases outside the respiratory system, such as cardiovascular disease, diabetes, childhood obesity, and cancer (Desikan, 2017 ; Mao et al, 2017 ; Maji et al, 2018 ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%